Stroke research productivity between the years of 2009 and 2013: Perspective of Turkey - Özdinçler, Arzu Razak; Tarakcı, Ela; Ersöz Hüseyinsinoğlu, Burcu; Tarakcı, Devrim (Wiley-Blackwell, 2014)
[Abstract Not Available]
WOS: 000345767700632
Keywords: Stroke Research Productivity; 2009 and 2013; Perspective of Turkey